Improved postprandial glucose control with ultra rapid lispro versus lispro with continuous subcutaneous insulin infusion in type 1 diabetes: PRONTO‐Pump‐2. Issue 7 (23rd March 2021) - Warren, Mark; Bode, Bruce; Cho, Jang I.; Liu, Rong; Tobian, Janet; Hardy, Thomas; Chigutsa, Farai; Phillip, Moshe; Horowitz, Barry; Ignaut, Debra
Abstract: Aim: To evaluate the efficacy and safety of ultra rapid lispro (URLi) versus lispro (Humalog ® ) in people with type 1 diabetes on continuous subcutaneous insulin infusion (CSII). Materials and Methods: This was a phase 3, 16‐week, treat‐to‐target study in patients randomized to double‐blind URLi (N = 215) or lispro (N = 217). The primary endpoint was change from baseline HbA1c (non‐inferiority margin 4.4 mmol/mol [0.4%]), with multiplicity‐adjusted objectives for postprandial glucose (PPG) levels during a meal test, and time spent in the target range 70–180 mg/dL (TIR). Results: URLi was non‐inferior to lispro for change in HbA1c, with a least‐squares mean (LSM) difference of 0.3 mmol/mol (95% confidence interval [CI] –0.6, 1.2) or 0.02% (95% CI –0.06, 0.11). URLi was superior to lispro in controlling 1‐ and 2‐h PPG levels after the meal test: LSM difference −1.34 mmol/L (95% CI –2.00, −0.68) or −24.1 mg/dL (95% CI –36.0, −12.2) at 1 h and −1.54 mmol/L (95% CI –2.37, −0.72) or −27.8 mg/dL (95% CI –42.6, −13.0) at 2 h; both p  < .001. TIR and time in hyperglycaemia were similar between groups but URLi resulted in significantly less time in hypoglycaemia (<3.0 mmol/L [54 mg/dL]) over the daytime, night‐time and 24‐h period: LSM difference −0.41%, −0.97% and −0.52%, respectively, all p  < .05. The incidence of treatment‐emergent adverse events was higher with URLi (60.5% vs. 44.7%), driven by infusion‐site reaction and infusion‐site pain, which was mostly mild or moderate. Rates of severe hypoglycaemia and diabetic ketoacidosis were similar between groups. Conclusions: URLi was efficacious, providing superior PPG control and less time in hypoglycaemia but with more frequent infusion‐site reactions compared with lispro when administered by CSII.